TAMING THE "FOREVER CHEMICALS": PFAS GOVERNANCE IN THE NETHERLANDS AS A WICKED PROBLEM - Rochmad Bayu Purnomoaji; M. Iip Wahyu Nurfallah; Surya Murdani (Pangripta Sembada : Jurnal Perencanaan Pembangunan, 2025)
This research aims to explain the role and influence of actors in three institutional domains namely the government (state), the industrial sector, and civil society in the governance of PFAS in the Netherlands. The research approach is qualitative with a case study of PFAS in the Netherlands. Data was collected through a comprehensive literature review of policies, scientific reports, and secondary sources related to PFAS. Data analysis was carried out using an institutional analysis approach and qualitative content analysis to examine the history of policies, actor interactions, and the dynamics of interests concerning the PFAS issue. Data accuracy was tested through source triangulation and cross-verification with official data to ensure information consistency. The Dutch government has issued PFAS regulations, including classifying PFAS as a hazardous chemical within the framework of environmental law. However, the implementation of these policies is hindered by policy fragmentation and a lack of harmonization with European Union regulations. The industrial sector maintains its economic interests through lobbying and the narrative of "essential use". This approach weakens regulatory enforcement efforts. However, public pressure encourages the industry to start innovating to reduce dependence on PFAS. Civil society (e.g., environmental NGOs and academics) plays a crucial role in advocacy, environmental litigation, and independent research to enhance government and industry transparency and accountability. In conclusion, cross-sectoral cooperation within a co-governance framework is needed to effectively address the PFAS problem. Close collaboration between the government, industry, and civil society will enhance transparency, accountability, and the alignment of public, economic, and environmental interests.